Representation of Western and Eastern Culture in Hayao Miyazaki Animation - Kuzmina, E V (KnE Engineering, 2018)
The article explores representation of Western and Eastern Culture using an example of Japanese animation of Hayao Miyazaki. By analyzing Miyazaki’s main images and techniques, the author shows the complexity and ambiguity of transcultural processes that, in turn, demand an expansion and revision of the main concepts of cross-cultural interaction. Keywords: Japanese animation, Eastern culture, Western culture, intercultural dialogue, interpretation, adaptation